The Dietary Supplement Label Database: Recent Developments and Applications. (3rd August 2018) - Dwyer, Johanna T; Bailen, Richard A; Saldanha, Leila G; Gahche, Jaime J; Costello, Rebecca B; Betz, Joseph M; Davis, Cindy D; Bailey, Regan L; Potischman, Nancy; Ershow, Abby G; Sorkin, Barbara C; Kuszak, Adam J; et al.
Abstract: Although many Americans use dietary supplements, databases of dietary supplements sold in the United States have not been widely available. The Dietary Supplement Label Database (DSLD), an easily accessible public-use database, was created in 2008 to provide information on dietary supplement composition for use by researchers and consumers. We describe in this article the history, key features, recent enhancements, and common applications of the DSLD. Accessing current information easily and quickly is crucial for documenting exposures to dietary supplements because they contain nutrients and other bioactive ingredients that may have beneficial or adverse effects on human health. This article details recent developments with the DSLD to achieve this goal, and provides examples of how the DSLD has been used. With periodic updates to track changes in product composition and capture new products entering the market, the DSLD currently contains >71, 000 dietary supplement labels. Following usability testing with consumer and researcher user groups completed in 2016, improvements to the DSLD interface were made. As of 2018, both a desktop and mobile device version are available. Since its inception in 2008, the DSLD has been used for research, exposure monitoring, and for other purposes by users in the public and private sectors. Further refinement of the user interface and search features is planned to facilitate ease of use for stakeholders. The DSLD can be used to track changes in product composition and capture new products entering the market. With >71, 000 dietary supplement labels, it is a unique resource that policymakers, researchers, clinicians, and consumers may find valuable for multiple applications.